Nursing a patient with bone arthralgia during pain attack treated by Traditional Chinese Medicine exercise therapy (“骨痹操”缓解1例骨痹患者疼痛效果观察及护理) - WANG Chun (王纯); TANG Ling (唐玲); LI Ye (李野); WANG Huaxin (王华新); LI Suqian (李苏茜); XU JingJin (徐京巾) (中西医结合护理)
This paper observed the effect of Traditional Chinese Medicine (TCM) exercise therapy on pain relief in a patient with bone arthralgia. Under the guidance of the theory of TCM nursing by syndrome differentiation, the TCM exercise therapy was carried out after implementation of nursing assessment and routine care. The TCM exercise therapy is effective to relieve the pain and improve the activity of daily of life. (本文总结“骨痹操”缓解1例骨关节炎患者疼痛的效果, 总结相关护理措施。在中医辨证施护的理论指导下, 护理人员完善护理评估和常规护理, 并开展“骨痹操”锻炼, 有效缓解疼痛, 提高日常生活活动能力。)